A Novel Model Incorporating Tumor Stiffness, Blood Flow Characteristics, and Ki-67 Expression to Predict Responses After Neoadjuvant Chemotherapy in Breast Cancer - Zhang, Jing; Gao, Song; Zheng, Qiaojin; Kang, Ye; Li, Jianyi; Zhang, Shuo; Shang, Cong; Tan, Xueying; Ren, Weidong; Ma, Yan (Frontiers in Oncology, 2020)
Objective: To investigate the ability of tumor stiffness, tumor blood flow, and Ki-67 expression alone or in combination in predicting the pathological response to neoadjuvant chemotherapy (NACT) in breast cancer. Patients and Methods: This prospective cohort study included 145 breast cancer patients treated with NACT. Tumor stiffness (maximum stiffness (Emax), mean stiffness (Emean) ) and blood score (BS), as well as their relative changes, were evaluated before (t0), during (t1–t5), and at the end of NACT (t6) by shear-wave elastography and optical imaging. Ki-67 expression was quantitatively evaluated by immunohistochemistry using core biopsy specimens obtained before NACT. Pathological responses were evaluated by residual cancer burden. The ability of tumor stiffness, BS, Ki-67, and predRCB—which combined ΔEmean (t2) (the relative changes in Emean after the second NACT cycles), BS2 (BS after the second NACT cycles), and Ki-67—in predicting tumor responses was compared using receiver operating characteristic curves and the Z-test. Results: Tumor stiffness and BS decreased during NACT. ΔEmean (t2), BS2, and Ki-67 had better predictive performance than other indexes in identifying a favorable response (AUC = 0.82, 0.81, and 0.80) and resistance responses (AUC = 0.85, 0.79, and 0.84), with no significant differences between the three (p > 0.05). PredRCB had better predictive performance than any parameter alone for a favorable response (AUC = 0.90) and resistance (AUC = 0.93). Conclusion: Tumor stiffness, BS, and Ki-67 expression showed good and similar abilities for predicting the pathological response to NACT, and predRCB was a significantly better predictor than each index alone. These results may help design therapeutic strategies for breast cancer patients undergoing NACT.